Foreign Direct Investment : Trends, Data Availability, Concepts, and Recording Practices - Patterson, Neil (Manuals and Guides, 2004)
The increasing importance of multinational enterprises in the global economy has stimulated interest in improving the availability, accuracy, and comparability of foreign direct investment (FDI) statistics among policymakers, analysts, and statisticians. This report notes recent trends in FDI and examines the progress made in moving toward compilation of FDI statistics in accordance with standards established by the IMF and the Organization for Economic Cooperation and Development (OECD). The report also reviews international recommendations for the compilation, analysis, and dissemination of FDI data and notes discrepancies in global balance of payments statistics and in data on bilateral FDI stocks. In addition, the report provides information on selected countries current practices in measuring FDI--on the basis of results from a joint IMF/OECD survey that covered 30 OECD countries and 31 other IMF member countries and was the subject of Foreign Direct Investment Statistics: How Countries Measure FDI 2001, published by the IMF and OECD in 2003.